2021
DOI: 10.1136/bmjebm-2021-111788
|View full text |Cite
|
Sign up to set email alerts
|

Risks of infection, hospital and ICU admission, and death from COVID-19 in people with asthma: systematic review and meta-analyses

Abstract: ObjectivesTo determine if and to what degree asthma may predispose to worse COVID-19 outcomes in order to inform treatment and prevention decisions, including shielding and vaccine prioritisation.DesignSystematic review and meta-analysis.SettingElectronic databases were searched (October 2020) for clinical studies reporting at least one of the following stratified by asthma status: risk of infection with SARS-CoV-2; hospitalisation, intensive care unit (ICU) admission or mortality with COVID-19.ParticipantsAdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
0
6
0
1
Order By: Relevance
“…[ 11 , 14 ] Systematic reviews and meta-analyses examining asthma alone have noted asthmatics are indeed less prone to adverse outcomes in the setting of COVID-19 infection. [ 22 , 23 ] The center for disease control and prevention behavioral risk factor surveillance system, which monitors the prevalence of asthma in the United States, reported 230,431 asthmatic patients in the state of Nevada in 2020, approximately 9.5% of the Nevada population. [ 24 ] Our study had 28 asthmatic patients admitted over 9 months, and a significant majority did not require intubation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 , 14 ] Systematic reviews and meta-analyses examining asthma alone have noted asthmatics are indeed less prone to adverse outcomes in the setting of COVID-19 infection. [ 22 , 23 ] The center for disease control and prevention behavioral risk factor surveillance system, which monitors the prevalence of asthma in the United States, reported 230,431 asthmatic patients in the state of Nevada in 2020, approximately 9.5% of the Nevada population. [ 24 ] Our study had 28 asthmatic patients admitted over 9 months, and a significant majority did not require intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Large systematic reviews and meta-analyses examining the comorbidity of asthma and Coronavirus have also failed to establish a clear association between adult asthma and severe outcomes of Coronavirus diseases. 57,58 While the relationship between asthma and adverse outcomes in Coronavirus diseases remains elusive, as mentioned earlier, ACE2 is involved in the regulation of type 2 inflammatory responses, primarily exerting a protective role against inflammation. Consequently, numerous studies have observed a reduced expression of ACE2 in asthma patients, leading to a decreased risk of adverse outcomes in Coronavirus diseases.…”
Section: Asthma and Ace2mentioning
confidence: 99%
“…Los pacientes asmáticos estaban siendo controlados en el programa GES de la institución, la mayoría eran adultos jóvenes con asma leve o moderada y estaban siendo manejados siguiendo las recomendaciones internacionales. Las revisiones sistemáticas descritas en la Tabla 5 confirman los mismos hallazgos, menor uso de recursos sani-tarios, riesgo de complicaciones y muerte en los pacientes asmáticos bien controlados [31][32][33][34][35][36][37][38][39][40][41][45][46][47][48][49][50] . En la revisión sistemática y metaanálisis de Halpin y cols.…”
Section: Lee B Et Al 2022unclassified